How to control cyclic nucleotide signaling by light. (December 2017) - Jansen, Vera; Jikeli, Jan F; Wachten, Dagmar
Graphical abstract: An optogenetic tool is composed of a photosensor domain, which absorbs light, and an effector domain, which executes the enzymatic function. Optionally, a targeting sequence for restricted expression in subcellular compartments can be added. Local light stimulation allows to control the enzymatic activity with high temporal and spatial resolution. Highlights: Optogenetics controls cyclic nucleotide signaling with spatio-temporal resolution. Genetic-engineering creates new tools by combining photosensory and effector domains. Optogenetic control of cyclic nucleotide signaling controls physiological functions. Abstract : Optogenetics allows to non-invasively manipulate cellular functions with spatio-temporal precision by combining genetic engineering with the control of protein function by light. Since the discovery of channelrhodopsin has pioneered the field, the optogenetic toolkit has been ever expanding and allows now not only to control neuronal activity by light, but rather a multitude of other cellular functions. One important application that has been established in recent years is the light-dependent control of second messenger signaling. The optogenetic toolkit now allows to control cyclic nucleotide-dependent signaling by light in vitro and in vivo .